PENGARUH PENERAPAN GREEN ACCOUNTING TERHADAP KUALITAS PENGUNGKAPAN CORPORATE SOCIAL RESPONSIBILITY DI PERUSAHAAN PUBLIK INDONESIA - Da Silva, Jose; Da Costa, Juvenal; Da Costa, Francisco; Pandin, Maria Yovita R.; Kusmaningtyas, Amiartuti (JURNAL KINDAI, 2025)
This study examines the effect of green accounting implementation on the quality of corporate social responsibility (CSR) disclosure in Indonesian public companies during the 2020–2024 period. The study is motivated by growing global demands for sustainable business practices and transparent social and environmental reporting. Secondary data were obtained from annual and sustainability reports of companies listed on the Indonesia Stock Exchange. A total of 112 firms were selected using purposive sampling. Data were analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM). The results indicate that green accounting has a positive and significant effect on CSR disclosure quality, with a path coefficient of 0.739 and a p-value below 0.001. These findings highlight the role of environmental accounting in enhancing corporate transparency and accountability and in supporting higher-quality sustainability reporting. Keywords: green accounting, CSR disclosure, sustainability reporting, environmental management, Indonesia